2000
DOI: 10.1094/phyto.2000.90.12.1322
|View full text |Cite
|
Sign up to set email alerts
|

Disease Development Following Infection of Tomato and Basil Foliage by Airborne Conidia of the Soilborne Pathogens Fusarium oxysporum f. sp. radicis-lycopersici and F. oxysporum f. sp. basilici

Abstract: Fusarium oxysporum f. sp. radicis-lycopersici, the causal agent of Fusarium crown and root rot of tomato, and F. oxysporum f. sp. basilici, the causal agent of Fusarium wilt in basil, are soilborne pathogens capable of producing conspicuous masses of macroconidia along the stem. The role of the airborne propagules in the epidemics of the disease in tomato plants was studied. In the field, airborne propagules of F. oxysporum f. sp. radicis-lycopersici were trapped with a selective medium and their prevalence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 17 publications
3
41
0
2
Order By: Relevance
“…The timing of symptom appearance and the severity of symptoms were almost the same on plants inoculated with wild-type and mutant strains, indicating that the ⌬FoSTUA mutants retained the abilities to infect host plant tissues and to cause disease symptoms under the conditions tested. F. oxysporum invades from roots of host plants, colonizes roots and stems, and produces conspicuous masses of macroconidia and microconidia on stem surfaces at the late stage of symptom development (26,44,45). We observed mycelia of wild-type and mutant strains growing on stem surfaces 3 weeks after inoculation.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The timing of symptom appearance and the severity of symptoms were almost the same on plants inoculated with wild-type and mutant strains, indicating that the ⌬FoSTUA mutants retained the abilities to infect host plant tissues and to cause disease symptoms under the conditions tested. F. oxysporum invades from roots of host plants, colonizes roots and stems, and produces conspicuous masses of macroconidia and microconidia on stem surfaces at the late stage of symptom development (26,44,45). We observed mycelia of wild-type and mutant strains growing on stem surfaces 3 weeks after inoculation.…”
mentioning
confidence: 88%
“…1D). These asexual spores play important roles in the disease cycle: macroconidia and microconidia are produced on the stem surfaces of infected plants and serve as secondary inocula to spread the fungus to neighboring host plants, and chlamydospores are endurance organs in soil and act as primary inocula when suitable host plants are planted in soil (17,26,39,44,45).…”
mentioning
confidence: 99%
“…Little evidence of correlation was observed in indicator detection and concentration between soil and fresh produce. This is not unexpected, as common regional farming practices (e.g., no nearby animal production facilities, use of synthetic fertilizers rather than compost, and use of plastic mulch), along with the arid growing conditions, likely minimized microbial contamination of soil in this production region (40)(41)(42). Although bivariate correlation analysis (Table 3) suggested that there was a significant negative correlation between microbial-indicator concentrations in irrigation and source water and indicator concentrations on produce, this relationship did not remain after adjustment for any linear model, except that for E. coli on produce and irrigation water (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Infection through leaf wounds by airborne propagules of F. oxysporum f. sp. radicis-lycopersici in tomatoes (Rekah et al, 2000) and F. oxysporum f. sp. basilici in basil (Uchida et al, 1996) have also been reported.…”
Section: Spore Trapping and Pathogenicity Testsmentioning
confidence: 98%